2016
DOI: 10.1111/1750-3841.13320
|View full text |Cite
|
Sign up to set email alerts
|

Phytic Acid: From Antinutritional to Multiple Protection Factor of Organic Systems

Abstract: Several studies have shown the benefits of natural antioxidants on health and food preservation. Phytic acid (IP6) is a natural antioxidant that is found mainly in cereals and vegetables and, for a long period of time, was considered an antinutritional factor. However, in vitro and in vivo studies have demonstrated its beneficial effects in the prevention and treatment of several pathological conditions and cancer. Despite the numerous benefits of IP6, the signs and intracellular interactions mediated by this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 76 publications
0
93
0
1
Order By: Relevance
“…Oats also contain other compounds such as phytic acid (5.6-8.7 mg/g; 0.56-0.87%) [9], which has its content decreased by 15%-35% during even a short three-day germination due to activation of phytase activity [50]. Although high doses of phytic acid inhibit the absorption of metals and minerals in humans, it has been observed that, in small doses, it can function as a protective factor in several chronic degenerative diseases [51]; therefore, current research only seeks to reduce the content of this antinutritional compound in various cereals.…”
Section: Discussionmentioning
confidence: 99%
“…Oats also contain other compounds such as phytic acid (5.6-8.7 mg/g; 0.56-0.87%) [9], which has its content decreased by 15%-35% during even a short three-day germination due to activation of phytase activity [50]. Although high doses of phytic acid inhibit the absorption of metals and minerals in humans, it has been observed that, in small doses, it can function as a protective factor in several chronic degenerative diseases [51]; therefore, current research only seeks to reduce the content of this antinutritional compound in various cereals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the observed phenotypes in IP6K-disrupted mice may arise from a decrease in 5-IP7 or an increase in IP6 or both. In cells, IP6 or 5-IP7 modulates various protein targets to regulate glycolysis, vesicular trafficking, chromatin remodeling, DNA damage, cell migration and neutrophil function, which may directly or indirectly alter energy metabolism in vivo [12,25,28,[94][95][96]. Moreover, IP6K1 regulates various targets by protein-protein interactions that do not require its catalytic activity [12,97,98].…”
Section: Bone Marrow Stem Cellsmentioning
confidence: 99%
“…Besides the already established PIP2 or IP3 [8,12,14,18,20,[23][24][25][26][27], glucose-6-phosphate and sphingolipids can also be precursors of Int-IP6 [23]. Int-IP6 regulates many cellular functions including stress responses, development, phosphate homeostasis, DNA repair, RNA editing, mRNA export and post-translational modification [94,95,189]. It also promotes insulin secretion from β cells, although to a lesser extent than 5-IP7 [81,190].…”
Section: Role Of the Ip6k Substrate Ip6 In Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex of phytic acid and some microelements in the form of phytate is negatively associated with mineral bioavailability, leading to a reduction in assimilation of bivalent cations (Frossard et al, 2000;Petry et al, 2014;Bohn et al, 2008). At the same time, phytates have antioxidant properties, and have a role in the reduction of risk of cancer and other pathologies (Vucenik and Shamsuddin, 2006;Silva and Bracarense, 2016). One of the goals of bean breeders has been to reduce phytate accumulation increasing the proportion of inorganic phosphorus.…”
Section: Introductionmentioning
confidence: 99%